The Role of Tumor-Stroma Interactions in Drug Resistance Within Tumor Microenvironment - Ni, Yanghong; Zhou, Xiaoting; Yang, Jia; Shi, Houhui; Li, Hongyi; Zhao, Xia; Ma, Xuelei (Frontiers in Cell and Developmental Biology, 2021)
Cancer cells resistance to various therapies remains to be a key challenge nowadays. For a long time, scientists focused on tumor cells themselves for the mechanisms of acquired drug resistance. However, recent evidence showed that tumor microenvironment (TME) is essential for regulating immune escape, drug resistance, progression and metastasis of malignant cells. Reciprocal interactions between cancer cells and non-malignant cells within this milieu often reshape the TME and promote drug resistance. Therefore, advanced knowledge about these sophisticated interactions is significant for the design of effective therapeutic approaches. In this review, we highlight cancer-associated fibroblasts (CAFs), tumor-associated macrophages (TAMs), tumor-associated neutrophils (TANs), myeloid-derived suppressor cells (MDSCs), T-regulatory lymphocytes (Tregs), mesenchymal stem cells (MSCs), cancer-associated adipocytes (CAAs), and tumor endothelial cells (TECs) existing in TME, as well as their multiple cross-talk with tumor cells, which eventually endows tumor cells with therapeutic resistance.